Toward Exploring Topographic Effects on Evolution and Propagation of Ocean Mesoscale Eddies Through Life Cycle Across Izu-Ogasawara Ridge in Northwestern Pacific Ocean - Nian, Rui; Geng, Xue; Zhang, Zhengguang; Yuan, Minghan; Fu, Zhen; Xu, Hengfu; Yang, Hua; Lai, Qi; He, Hui; Su, Chi Wei; Zang, Lina; Yuan, Qiang; et al. (Frontiers in Marine Science, 2022)
Ocean mesoscale eddies contribute significantly to water transport on a global scale, constituting the ubiquitous, irregular, discrete, nonlinear components. In this manuscript, we propose to explore whether and how the topographic effect of one meridional ridge, could exert considerable influences on the evolution and propagation of mesoscale eddies through their life cycle, directly from the perspectives of real observation statistics. We systematically investigate the known variability of mesoscale eddy trajectories, derived by multimission satellite altimetry from 1993 to 2018, of a life cycle more than 6 months, over the Izu-Ogasawara Ridge, and quantitatively examined the eddy-ridge interaction by observation statistics and wavelet coherence map, with respect to the intrinsic attributes, namely, the amplitude, the rotation speed, the radius. Due to the spatial-temporal diversity, a series of correlative steps have been particularly designed along time-frequency domain to trace back mesoscale eddy trajectories in a variety of origins, location, lifespan, polarity, either completely or partially passing over the ridge, and to facilitate the standardization in statistics across three phases of their life cycle, i.e., before, during and after the interaction with the ridge. It has been revealed in our experiment that three intrinsic attributes of mesoscale eddies within 25 years, all demonstrated noticeable correlation with the variation of topographic relief over the ridge. We observed that most of the cyclonic eddies obviously tended to begin to decay or even demise, while on the contrary, some of the anticyclonic eddies preferred to intensify slightly, or making no significant difference when encountering the upslope until climbing across the top, basically consistent with the expectation of potential vorticity (PV) conservation. The drifting velocity agreed with the tendency that the direction would be more probably modified toward equatorward or poleward by forcing to meridional component, with zonal component reduced at the beginning. The mesoscale eddies with the passage over the ridge exhibited the relatively high average horizontal scales, amplitude, rotation speed on the whole, compared to those with only partially passage. The developed scheme could integrate more evidences on how mesoscale eddies response to the topographic effects during their time-varying evolution and propagation process, and help provide opportunities to potentially identify and predict the underlying dynamic patterns and mechanisms that mesoscale eddies engage in ocean dynamics when proceeding toward meridional ridges on a global scale, with the promise of the end-to-end data-driven solution, such as deep learning architecture involved in the future.